Novos modelos de ocupação urbana: os condomínios fechados horizontais em Goiânia - Souza, Renato Medeiros de (2012)
The present study sought to analyze and understand the reason for the existence and growth of gated communities in Goiania. This type of housing arises in the 1970s, but recently received a new impulse, which demonstrates the desire for security and exclusivity of collective spaces. The search for security, in constant flight of urban violence has contributed to the increase of this type of housing. The results show that the environment of horizontal condominiums has good security, being the main aspects related to that the presence of physical barriers that surround the restricted and controlled access and other security devices such as cameras and closed circuit TV. Therefore, to analyze and contextualize this process was the basis for the discussion of this work.